Designing biomaterials with immunomodulatory properties for tissue engineering and regenerative medicine. Issue 2 (16th May 2017) - Andorko, James I.; Jewell, Christopher M.
Abstract: Recent research in the vaccine and immunotherapy fields has revealed that biomaterials have the ability to activate immune pathways, even in the absence of other immune‐stimulating signals. Intriguingly, new studies reveal these responses are influenced by the physicochemical properties of the material. Nearly all of this work has been done in the vaccine and immunotherapy fields, but there is tremendous opportunity to apply this same knowledge to tissue engineering and regenerative medicine. This review discusses recent findings that reveal how material properties—size, shape, chemical functionality—impact immune response, and links these changes to emerging opportunities in tissue engineering and regenerative medicine. We begin by discussing what has been learned from studies conducted in the contexts of vaccines and immunotherapies. Next, research is highlighted that elucidates the properties of materials that polarize innate immune cells, including macrophages and dendritic cells, toward either inflammatory or wound healing phenotypes. We also discuss recent studies demonstrating that scaffolds used in tissue engineering applications can influence cells of the adaptive immune system—B and T cell lymphocytes—to promote regenerative tissue microenvironments. Through greater study of the intrinsic immunogenic features of implantable materials and scaffolds, new translational opportunities will arise to better control tissue engineering and regenerative medicine applications. Abstract : New research has revealed that the physicochemical properties of biomaterials can activate immune pathways, even in the absence of other stimulatory immune cues. While nearly all of this work has been in the vaccine and immunotherapy fields, this same knowledge could inform new tissue engineering and regenerative medicine strategies. This review discusses recent findings that reveal how material properties—size, shape, chemical functionality—impact both innate and adaptive immune responses in ways that could be harnessed for next generation tissue engineering and regenerative medicine applications.